Cover Image, Volume 138, Issue 40. Issue 40 (16th July 2021) - Ali, Nisar; Ali, Farman; Said, Amir; Khurshid, Sania; Sheikh, Zeshan Ali; Ali, Usman; Nguyen‐Tri, Phuong; Bilal, Muhammad
Abstract : The cover image by Muhammad Bilal and colleagues shows an SEM micrograph representing the fractured surface of clay reinforce sulfonated polyimide nanocomposite. The SPI membrane characterizes a homogenous morphology throughout the matrix due to the uniform distribution of clay nanoparticles with no pore or cracks. The uniform distribution and proper dispersion of nanofillers are due to the functionalization of vermiculite clay, as the NH2 group of 3‐APTES makes contact through covalent linkage with the SO3 H group of SPIs matrix. However, these linkages between organicinorganic moieties might affect the properties of composites film. DOI: 10.1002/app.51310